Iron-fortified parboiled rice - A novel solution to high iron density in rice-based diets - Chanakan Prom-u-thai (2018)
The present study pioneered an investigation of a novel and cost-effective approach to fortify Fe in rice and to greatly improve Fe nutrition in rice-based diets through parboiling, though it remains at its preliminary phase. Rice grains of seven cultivars were parboiled in deionised water containing different levels of Fe chelate made by mixing different proportions of Fe sulfate (FeSO4) with ethylenediaminetetra-acetic acid disodium salt (Na2EDTA). Adding Fe to the parboiling water resulted in an increased Fe concentration in the most grain, effectively where FeSO4and Na2EDTA were mixed at 2:1 molar ratio (11.16 g Fe per 100 g raw paddy grain). This treatment resulted in Fe concentrations in white rice milled for 60 s and 120 s, which were 20-50 times higher than those in the unfortified milled raw rice grains. The Fe concentrations in milled rice grains were 50-150 mg Fe kg-1in 60 s milled grains with a slight reduction in 120 s milled grains. Perls Prussian blue staining of the cross section of Fe-fortified parboiled rice grains suggested inward movement of added Fe into the endosperm through the apoplastic pathway in the dorsal region of the rice grain. The retention rates of fortified Fe varied among the different cultivars, possibly due to different physical-chemical properties of the grains. The percentages of soluble fraction of the total Fe were higher than 50% in all cultivars tested, indicating its high bioavailability potential, though it remains to be evaluated. The present findings provided a preliminary basis for further investigation of this innovative technique, before its adoption by parboiled rice industry, such as optimising the levels of Fe addition and industrial process and Fe bioavailability in Fe-fortified-parboiled rice. Crown Copyright © 2008.